Evaluation of infectious bursal disease virus stability at different conditions of temperature and pH. Issue 6 (November 2015) - Rani, Surabhi; Kumar, Sachin
Abstract: Infectious bursal disease (IBD) is one of the highly pathogenic viral diseases of poultry. The disease poses a serious threat to the economy of many developing countries where agriculture serves as the primary source of national income. Infectious bursal disease virus (IBDV) belongs to the family Birnaviridae . The IBDV is well characterized to cause immunosuppression in poultry. The live attenuated vaccine is the only way to protect the chickens from IBDV infection. The ineffectiveness of vaccine is one of the major causes of IBDV outbreaks in field condition. In the present study, we discuss briefly about the biology of IBDV genome and its proteins under different conditions of temperature and pH in order to evaluate its infectivity under adverse physical conditions. Our results indicate that the IBDV is non-infective above 42 °C and unstable above 72 °C. However, the change in pH does not significantly contribute to the IBDV stability. The study will be useful in estimating an optimum storage condition for IBDV vaccines without causing any deterioration in its viability and effectiveness.